A new report of adult Hyalomma marginatum and Hyalomma rufipes in the Czech Republic - Lesiczka, Paulina Maria; Daněk, Ondřej; Modrý, David; Hrazdilová, Kristýna; Votýpka, Jan; Zurek, Ludek (Ticks and tick-borne diseases, 2022)
Hyalomma marginatum and Hyalomma rufipes are important vectors of Crimean-Congo Hemorrhagic Fever Virus (CCHFV) in North Africa and Southern Europe. They are occasionally also reported from Central and Western Europe where they are likely introduced from their natural range by migratory birds. In this study, we report findings and molecular identification of adults and one nymph of H. marginatum and H. rufipes, primarily from horses from different regions of the Czech Republic. While the number of the reported ticks is small, this is likely to be an underrepresentation of the actual number. Due to their vector competence for CCHFV and potential expansion into new areas with a changing climate, surveillance programs in Europe are warranted.
Keywords: Animals; Imported ticks; Hyalomma marginatum; lidé; Migratory birds; Ixodidae; Hemorrhagic Fever, Crimean; Hyalomma rufipes; koně; Horses; Hemorrhagic Fever Virus, Crimean-Congo; klíšťata; Ticks; Czech Republic; hemoragická horečka krymská; virus krymsko-konžské hemoragické horečky; Česká republika; zvířata; Humans